Marketing Two Immunization Services at a Regional Supermarket Chain Pharmacy - Megan A. Hedden; Yifei Liu; Peggy G. Kuehl; Sarah M. Oprinovich (Pharmacy, 2023)
Background: Personal selling of immunization services includes starting a dialogue with patients, utilizing effective questioning and listening skills to identify their vaccination needs, and recommending appropriate vaccines accordingly. The study objectives were (1) to integrate personal selling into the dispensing workflow to promote pneumococcal polysaccharide vaccine (PPSV23), and (2) to evaluate the impact of personal selling and automated telephone calls to promote herpes zoster vaccine (ZVL). Methods: For the first study objective, a pilot project was conducted at one out of 19 affiliated supermarket pharmacies. Dispensing records were used to target patients with diabetes mellitus for PPSV23, and personal selling was implemented over a 3-month period. For the second study objective, a full study was conducted among the nineteen pharmacies, with five in the study group and 14 in the control group. Personal selling was implemented over a 9-month period, and automated telephone calls were placed and tracked over a 6-week period. Mann–Whitney U tests were used to compare vaccine delivery rates between the study and control groups. Results: In the pilot project, 47 patients needed PPSV23, but none received it from the pharmacy. In the full study, 900 ZVL vaccines were given, with 459 given for 15.5% of the eligible patients in the study group. During the time when 2087 automated telephone calls were placed and tracked, 85 vaccines were given across all pharmacies, with 48 given for 1.6% of the eligible patients in the study group. During both the 9-month and 6-week periods, the mean ranks of vaccine delivery rates in the study group were higher than the control group (p < 0.05). Conclusions: The pilot project incorporated personal selling into the dispensing workflow and, although no vaccines were given, provided valuable lessons. The full study demonstrated that personal selling alone and personal selling combined with automated telephone calls were associated with higher vaccine delivery rates.